Predictive value of ultrasonographic assessment of disease activity in response to tumour necrosis factor-a inhibitor treatment in rheumatoid arthritis: A prospective cohort study - (:unkn) unknown (Clinical and Experimental Rheumatology S.A.S., 2016)
[No abstract available]